Introduction in the educational process of the results of the study changes in bloood cells in animals after administration of sorbent (Eurasian Journal of Ecology, 2018)
This process is implemented using a variety of functions of the organism. Trials showed that under the influence of extreme factors in thebody has been adapted embodied reactions involving the lymph system.The Results has been observed that under the influence of extreme factorsand motility lymph lymph node, lymph structure completely changed. Thestudy of result revealed the influence of toxic substances on the lymphaticsystem. In the group which got toxic substances a long time, changes ofblood viscosity and lymph, the overall composition of the protein, bloodpressure, observed small changes of ion concentration C. In our experience, we use SUMS-1 (1g / kg) as a detoksikant, after its application impact toxic substances has decreased and the condition of animals is muchimproved. In general, speaking about the composition of lymph and theflow of lymph, there are elements of blood cells and physico-chemical andbiochemical index positive results. When using the organic decline wasenterosorbents detoxifiers in lymph flow and composition of lymph. Afterget sorbents blood cell recovery record shows that (SUMS-1) high sorptionproperties. In turn, after the poisoning, the use of sorbents SUMS-1 setchanges in the body that speaks about his recovery. This work shows thatresearch in this area should continue.Key words: lympha, sorbent, erythrocyte, leucocyte, lymphocyte, hemoglobin, tetrahlormethane.